WASPADA EPIDEMI HIV-AIDS DI INDONESIA - Handayani . (Jurnal Ilmu Kesehatan dan Kesehatan, 2017)
One of the major health problem in Indonesia is the spreading of Acuquired Immune Deficiency Sidrome(AIDS) and Human Immuno Deficiency Virus(HIV). The development of HIV-AIDS in Indonesia is veryalarming. The high number of people living with HIV-AIDS will affect on demography structure, health caresystems, national economic and social order. Combating HIV-AIDS face a variety of complex challenges,requiring both a policy and action at the national, regional, and global. How to coverage prevention andtreatment of HIV-AIDS, strengthening the quality of health services, assurance of drug availability,appropriate and effective regulation, elimination of stigma and discrimination, as well as tests and treatmentsfor patients. Indonesian government have to involve various parties in HIV-AIDS, especially from the fieldof socio-cultural, educational, and religious for the prevention and improvement of patient care need tochange people's behavior.